Selecting high priority activities for the reallocation of resources to reduce construction duration - Lee, Chijoo (Journal of Civil Engineering and Management, 2022)
It is difficult to identify economically feasible alternatives to reduce the duration of construction, as many important factors are present in any given construction project, such as increased construction costs and incentives and decreased delay liquidated damages. Most importantly, thousands of activities are interconnected in a complicated manner. This study proposes a method for analyzing the priority of activities for the reallocation of resources in order to reduce construction delay duration. The proposed method is composed of two steps: the prioritization of activities that can reduce construction duration and a reallocation of resources based upon that prioritization. First, in order to analyze priority, combinations of the lowest-cost activities for reducing per day are derived. Then, the importance of influence factors is analyzed, using the fuzzy analytic hierarchy process and fuzzy inference, and priority is derived based on the importance level. Next, the resources are reallocated based on the objective functions of maximizing the importance of the selected activities, reducing the duration, and minimizing the reducing cost. Decision-makers can compare between the reduction duration and available cost, and compare between results of the proposed method and the existing cost-slope method. Then, decision-makers can use the proposed method differently based on their own preferences toward economic and qualitative importance.